PENINGKATAN EFISIENSI KEUANGAN DAN BISNIS ECOPRINT EIKORA MELALUI PELATIHAN DAN PENDAMPINGAN DI PADANG PANJANG - Rayna Kartika; Sanda Patrisia Komalasari; Laura Amelia Triani; Rahma Dini Putri; Naila Nurul Afifah; Andes Setia; Fhirasa Istivani (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
The objective of this activity is to improve the financial management efficiency of UMKM Ekoprint Eikora in Padang Panjang, West Sumatra, through comprehensive training and assistance related to financial management. The main focus is to help partners create more structured financial records, prepare annual budgets, and improve understanding of effective financial management to support the business's stability and sustainability. The methods used include intensive training in daily transaction recording, financial reporting, and operational budget planning. Mentoring is carried out directly through discussions, simulations, and evaluations to ensure optimal understanding in applying a better financial system. The results show that UMKM Eikora successfully improved the efficiency of financial recordkeeping, which was previously done manually, to become more systematic and digital-based. The preparation of the annual operational budget was successfully implemented with better cost control indicators, and the financial team’s ability to understand and use financial reports for business decision-making also significantly improved. This step supports more effective financial management, enhances business stability, and strengthens competitiveness in the market. The conclusion of this activity is that training and assistance in financial management have a positive impact on the efficiency and sustainability of UMKM Eikora. Recommendations for sustainability include further training in financial analysis and regular monitoring of the implementation of the financial system.